Rearranging Edgeworth-Cornish-Fisher expansions - Victor Chernozhukov; Iván Fernández-Val; Alfred Galichon (Centre for Microdata Methods and Practice (cemmap), 2007)
This paper applies a regularization procedure called increasing rearrangement to monotonize Edgeworth and Cornish-Fisher expansions and any other related approximations of distribution and quantile functions of sample statistics. Besides satisfying the logical monotonicity, required of distribution and quantile functions, the procedure often delivers strikingly better approximations to the distribution and quantile functions of the sample mean than the original Edgeworth-Cornish-Fisher expansions.
Keywords: 330; Schätztheorie; Statistische Verteilung; Theorie